When and where does foreign direct investment generate positive spillovers? A meta-analysis - Meyer, Klaus E; Sinani, Evis (Journal of International Business Studies, 2009)
Local firms may attract productivity spillovers from foreign investors, yet these vary with local firms' awareness, capability and motivation to react to foreign entry. In consequence, spillovers vary across countries at different levels of economic development. We apply competitive dynamics theory to analyze these contextual moderators of spillovers, and test hypotheses thus derived in a meta-analysis of the empirical literature on spillovers. Our analysis suggests a curvilinear relationship between spillovers and the host country's level of development in terms of income, institutional framework and human capital.